A histopathological and clinical assessment on the effect of microneedling on the autologous platelet-rich plasma in the experimental wound healing model (Annals of Medical Research, 2021)
Aim: Platelet Rich Plasma (PRP) is a method used in dentistry and aesthetic applications in order to accelerate tissue healing. The purpose of this study is to assess the effect of PRP on accelerating wound healing and the contribution of microneedling application, i.e. multiple injection during PRP, and the volume effect of the PRP material to healing.Materials and Methods: In the study, 16 5-month-old male white New Zealand rabbits with an average weight of 2.7-3.0 kg were used. The four wounds were made on the back of each rabbit, and PRP, Normal saline(NS), microneedling(MN), and Sham procedures applied. Eight rabbits were sacrificed by taking their tissues for histological assessment at the end of 14 days. Epithelization, VEGF expression, angiogenesis, inflammatory cell, fibroblast, reticular fiber, and collagen parameters were evaluated. Eight rabbits were followed up for macroscopic healing.Result: The PRP procedure decreased the healing duration and wound area compared to other procedures(p